(untitled) (Research, Society and Development, 2022)
Medicalization is a historically constituted phenomenon, which covers the realms of education, health, culture, work, industry and in last social relations and subjective experiences. It is a scientistic project that encompasses from both reductionist and individualizing perspective, health-disease processes that involve complex, diverse and interrelated aspects of existence, biological, psychological, social, historical, structural, institutional. Bearing in mind the presence of this phenomenon in the daily life issues of our time, this research was aimed at understanding and mapping the perceptions and experiences of the population regarding three possible experiences: changes in sleep, appetite, motivation and concentration. Therefore, a virtual questionnaire was carried out to evaluate the frequency and reasons identified by the individuals in such given phenomena. The data were analyzed by quantitative and qualitative-theoretical methodology and indicated a prevalence, higher than 90%, in each phenomenon. It is also observed that in 60 to 80% of cases the subjects associate sleep, appetite and motivation changes with problems of daily life, such as overwhelming tasks, economic and relationship problems. The results show on the one hand a significant association between such changes and experiences in the life context of those affected, which implies a risk of a structural precariousness of the quality of life and on the other hand the risks of medicalization without the contextualization of such situations. This scenario is an alert for health professionals, whose diagnostic practice may prematurely pathologize individual phenomena of complex formation.